An Analysis of Social Values and Characteristics of the Main Character in Hafalan Shalat Delisa Novel - Rafidah Hanim; Siti Sarah Fitriani; Nurul Inayah (Universitas Syiah Kuala, 2021)
The objective of this study is to find out the social values and characteristics of main character in Hafalan Shalat Delisa Novel written by Tere Liye. In this study the researcher used qualitative methods. The researcher read the novel Hafalan Shalat Delisa and then explored the social values and characteristics of main character contain in the novel. Hafalan Shalat Delisa Novel is a novel that tells about a six-year-old girl and her family who were hit by a tsunami disaster in Aceh on December 26, 2004. The novel describes about Acehnese girl name Delisa, a Tsunami Victim and how she survived. This study was conducted to analyze the social values and characteristics of main character in the novel. The social values contained in this novel are education, religious, caring others, honesty, affection, friendship, mutual, and helping others. Moreover, the characteristics of the main character contained in this novel are appreciate, quick in imitating other’s speech, kind, carious, forgetful and never giving up.